Assessment of Endotracheal Tube Position After Oral Intubation in Neonates - Ali Gül; Şahin Takçı; Deniz Anuk İnce; Şeyma Ünüvar (Galenos Yayinevi, 2018)
Aim: Endotracheal intubation is a common procedure in the delivery room and neonatal intensive care unit. We aimed to determine the accuracy of this method of endotracheal tube (ETT) placement in our neonatal cohort. Materials and Methods: Data on infants requiring oral intubation were reviewed retrospectively. The initial ETT depth of insertion had been calculated using the Tochen 7-8-9 rule. The initial depth was compared to the mid-tracheal region. The differences between the initial and ideal depth was calculated and divided by the mid-tracheal distance. Infants were grouped according to their weights as ≤1000 g, 1001 to 2000 g, 2001 to 3000 g and ≥3001 g. Results: We evaluated ETT placement in 160 neonates. The mean gestational age was 32.2±4.4 weeks (23 to 41 weeks) and the mean weight was 1989±829 g (560 to 3800 g). The mean range of the difference between the initial depth and ideal depth divided by mid-tracheal distance was 0.39±0.04, 0.35±0.04, 0.46±0.05, and 0.23±0.04 in infants weighing ≤1000 g, 1001 to 2000 g, 2001 to 3000 g and ≥3001 g respectively (p=0.025). The differences between the 2001-3000 g group and the 1001-2000, also the 2001-3000 g group and the ≥3001 g group were statistically significant (p<0.05). Conclusion: The 7-8-9 rule should be used to assess ETT length in neonates, especially in those weighing more than 3 kg. As this rule has low accuracy for extremely low birth weight neonates, its reliability may not be high for neonates weighing less than 3 kg in weight.